1970
DOI: 10.1139/v70-077
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance spectroscopic study of radicals derived from glycine, dl-α-alanine, and β-alanine in aqueous solution

Abstract: The substrates glycine, dl-u-alanine, and B-alanine have been examined in turn within an aqueous continuous-flow system using the titanous chloride -hydrogen peroxide radical-generating method.The temperature was 25 i 2 "C and the p H of the reaction mixture was varied within the range of values ca. 2 to ca. 5 by addition of sulfuric acid. The electron paramagnetic resonance spectra of the following transient radicals were observed: from glycine, .CH(NHZ)COOH; from dl-a-alanine, CH3C(NNZ)COOH and .CH2CH(NH3+)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…303,[312][313][314][315][316][317] Hydrogen abstraction in general occurs predominantly away from the (protonated) amino group, and abstraction adjacent to hydroxyl groups is more facile than abstraction at unactivated positions. Neta and Fessenden (312) used pulse radiolysis in the cavity of an ESR spectrometer to study the reactions between O H raqicals and organic substrates and concluded that a-distonic amine ions, e.g., 'CH2NH(CH3)2 122, were formed from amines under acidic conditions.…”
Section: Hydrogen Abstraction From A~~o N~~~n Ions In Aqueous Solutionmentioning
confidence: 99%
“…303,[312][313][314][315][316][317] Hydrogen abstraction in general occurs predominantly away from the (protonated) amino group, and abstraction adjacent to hydroxyl groups is more facile than abstraction at unactivated positions. Neta and Fessenden (312) used pulse radiolysis in the cavity of an ESR spectrometer to study the reactions between O H raqicals and organic substrates and concluded that a-distonic amine ions, e.g., 'CH2NH(CH3)2 122, were formed from amines under acidic conditions.…”
Section: Hydrogen Abstraction From A~~o N~~~n Ions In Aqueous Solutionmentioning
confidence: 99%
“…The a^_H is in good agreement with previous values. 15 The hyperfine coupling constant due to the ß proton is relatively small, approximately [1][2][3][4][5] G, when it is a methine proton. This spectrum could be assigned to either or both structures A obtained whenever the pH 11.5 procedure was applied, even though the others were not.…”
Section: Resultsmentioning
confidence: 99%
“…t-BuN=0 + R.-> t-BuN(0-)R (1) Each ESR spectrum of each spin adduct shows a primary 14N triplet from the nitroxide nitrogen, and secondary splittings are used for the identification of the spin adducts. However, since ESR spectra obtained from aqueous solutions of biomolecules that are irradiated and simultaneously spin trapped by using MNP are too complex to identify completely owing to overlapping of many signals of the spin adducts present, it was found necessary to separate them individually.…”
Section: Introductionmentioning
confidence: 99%